Measurements of water uptake of maize roots: the key function of lateral roots - Ahmed, Mutez A; Zarebanadkouki, Mohsen; Kaestner, Anders; Carminati, Andrea (Plant and soil, 2016)
AIMS: Maize (Zea mays L.) is one of the most important crops worldwide. Despite several studies on maize roots, there is limited information on the function of different root types in extracting water from soils. Aim of this study was to investigate the location of water uptake in maize roots. METHODS: We used neutron radiography to image the spatial distribution of maize roots in soil and trace the transport of deuterated water (D₂O) in soil and roots. Maize plants were grown in aluminum containers filled with a sandy soil that was kept homogeneously wet throughout the experiment. When the plants were 16 days old, we injected D₂O into selected soil regions. The transport of D₂O was simulated using a diffusion–convection numerical model. By fitting the observed D₂O transport we quantified the diffusion coefficient and the water uptake of the different root segments. RESULTS: The root architecture of a 16 day-old maize consisted of a primary root, 4–5 seminal roots and many lateral roots. Laterals emerged from the proximal 15 cm of the primary and seminal roots. During both day and night measurements, D₂O entered more quickly into lateral roots than into primary and seminal roots. The quick transport of D₂O into laterals was caused by the small radius of lateral roots. The diffusion coefficient of lateral roots (4.68 × 10⁻⁷ cm² s⁻¹) was similar to that of the distal unbranched segments of seminal roots (4.72 × 10⁻⁷ cm² s⁻¹) and higher than that of the proximal branched segments (1.42 × 10⁻⁷ cm² s⁻¹). Water uptake of lateral roots (1.64 × 10⁻⁵ cm s⁻¹) was much higher than the uptake of seminal roots, which was 5.34 × 10⁻¹⁰ cm s⁻¹ in the proximal branched segments and only 1.18 × 10⁻¹² cm s⁻¹ in the distal unbranched segments. CONCLUSIONS: We conclude that the function of lateral roots is to absorb water from the soil, while the function of the primary and seminal roots is to axially transport water to the shoot.